Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Saving Behavior Mahasiswa di Universitas Teuku Umar - Ulva Widayanti; Fitria Mandaraira; Tamitha Intassar Husen (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of financial literacy and financial inclusion on the saving behavior of students at Teuku Umar University. This study employed a quantitative approach with an associative research design. The population consisted of 5,520 active students at Teuku Umar University, with a sample of 382 respondents selected using the proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS version 4.1.1.4. The results indicate that financial literacy has no significant effect on students' saving behavior (t-statistics = 1.545; p-value = 0.123), whereas financial inclusion has a positive and significant effect on students' saving behavior (t-statistics = 10.102; p-value = 0.000). The Adjusted R Square value of 0.211 indicates that financial literacy and financial inclusion jointly explain 21.1% of the variance in students' saving behavior, while the remaining 78.9% is explained by other variables outside the research model. This study concludes that financial inclusion is a more dominant factor influencing students' saving behavior than financial literacy.